Pengelolaan Dana Bos Di SMP Negeri 2 Soa Kecamatan Soa Dalam Upaya Menghasilkan Laporan Pertanggungjawaban Keuangan Yang Akuntabel Periode 2020-2022 - Beatriks Doke Meo; Dwi Anggarani; Khojanah Hasan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research is about the Management of BOS Funds at SMP Negeri 2 Soa, Soa District in an Effort to Produce Accountable Financial Responsibility Reports (2020-2022 Period). To find out about the management of BOS Funds at SMP NEGERI 2 SOA in an effort to produce accountable financial responsibility reports. in this research is descriptive qualitative with data collection techniques using interviews, observation and documentation studies. The informants in this research are the principal, treasurer, teachers, committee. The results of the research show that the management of BOS funds at SMP Negeri 2 Soa has been going well as seen from a form of accountability that is in accordance with the BOS Fund technical guidelines and has produced accountable financial reports.